Employee Work Motivation in the Pamong Praja Police Unit, Public Protection and Fire in Gorontalo Province - Foni Ibrahim; Widya Kurniati Mohi; Nur Eng Mokodompit (Journal of Public Representative and Society Provision, 2021)
This study aims to obtain an overview of the Work Motivation of Employees in the Civil Service Police Unit, Gorontalo Province Community and Fire Protection. The research method uses a qualitative type with a qualitative approach. Data collection techniques carried out through interviews with a number of informants and observations and recording secondary data related to research problems. The results of the study concluded that the motivation of Employee Work in the Civil Service Police Service Unit, Gorontalo Province Community and Fire Protection has not been fully implemented. Likewise, the indicators of social relations still need to be improved so that there is good communication between people, meaning that the work done is still overlapping, resulting in a lack of enthusiasm in completing work. The need for security indicates that employees have work certainty, even though it has not run optimally. Caused by inappropriate workloads make employees uncomfortable at work. While the need for recognition shows that employees who excel are given an award, although not all because there are still employees who do not adhere to the regulations in force.